1991
DOI: 10.1007/bf01955527
|View full text |Cite
|
Sign up to set email alerts
|

Cystic fibrosis presenting with recurrent vomiting and metabolic alkalosis

Abstract: Between January 1980 and December 1987, ten Saudi Arabian children at Saudi Arabian Oil Co. (Saudi Aramco) health care facilities in the Eastern Province of Saudi Arabia had cystic fibrosis (CF). The incidence of CF in Saudi Arab children less than or equal to 14 years was 1 in 4243. Five of the ten children had hypoelectrolytaemia and metabolic alkalosis on initial presentation. Two of the five had recurrent vomiting, hypoelectrolytaemia and metabolic alkalosis alone and initially no chest symptoms. Early exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…19 Again, a further 10 children from the Eastern Province were documented as having CF in 1991, and Mathew et al suggested an incidence of 1 in 4243 for Saudi children. 20 Again, as previously described in Kuwait, vomiting and metabolic alkalosis associated with the high ambient temperatures in the summer months were associated with the presentation in these patients. A review by Nazer and Rahbeeni of their experiences of CF included 36 patients seen by them from 1986 to 1992.…”
supporting
confidence: 69%
“…19 Again, a further 10 children from the Eastern Province were documented as having CF in 1991, and Mathew et al suggested an incidence of 1 in 4243 for Saudi children. 20 Again, as previously described in Kuwait, vomiting and metabolic alkalosis associated with the high ambient temperatures in the summer months were associated with the presentation in these patients. A review by Nazer and Rahbeeni of their experiences of CF included 36 patients seen by them from 1986 to 1992.…”
supporting
confidence: 69%
“…The incidence of CF in the United Arab Emirates and Saudi Arabia is 1:16,000 and 1:4,000, respectively [ 4 , 5 ], while in Caucasian populations it is approximately 1:2,500, with comparable carrier rates throughout North America, the UK and Europe [ 6 ]. Eight thousand people are currently living with CF in the UK, with a median predicted survival of 41.5 years [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…These cases are usually difficult to correct and treatment needs modified oral rehydration solution [13-15]. Patients with CF are also at risk of increased gastrointestinal and insensible fluid losses [16]. In addition, 5-17 % of CF patients are at risk of developing CFRD due to pancreatic endocinopathy [17-20].…”
Section: Discussionmentioning
confidence: 99%